Prognostic value of primary tumor sidedness in patients with non-metastatic IBD related CRC – Is it the exception to the rule?. (December 2022) - Kamphues, Carsten; Lefevre, Jeremie H.; Wang, Jane; Amini, Neda; Beaugerie, Laurent; Kuehn, Florian; Park, Sang Hyoung; Andreatos, Nikolaos; Lauscher, Johannes C.; Enea, Diana; Lehmann, Kai S.; Peru, Nicolas; et al.
Abstract: Background: Although primary tumor sidedness (PTS) has a known prognostic role in sporadic colorectal cancer (CRC), its role in Inflammatory Bowel Disease related CRC (IBD-CRC) is largely unknown. Thus, we aimed to evaluate the prognostic role of PTS in patients with IBD-CRC. Methods: All eligible patients with surgically treated, non-metastatic IBD-CRC were retrospectively identified from institutional databases at ten European and Asian academic centers. Long term endpoints included recurrence–free (RFS) and overall survival (OS). Multivariable Cox proportional hazard regression as well as propensity score analyses were performed to evaluate whether PTS was significantly associated with RFS and OS. Results: A total of 213 patients were included in the analysis, of which 32.4% had right-sided (RS) tumors and 67.6% had left-sided (LS) tumors. PTS was not associated with OS and RFS even on univariable analysis (5-year OS for RS vs LS tumors was 68.0% vs 77.3%, respectively, p = 0.31; 5-year RFS for RS vs LS tumors was 62.8% vs 65.4%, respectively, p = 0.51). Similarly, PTS was not associated with OS and RFS on propensity score matched analysis (5-year OS for RS vs LS tumors was 82.9% vs 91.3%, p = 0.79; 5-year RFS for RS vs LS tumors was 85.1% vs 81.5%, p = 0.69). These results were maintained when OS and RFS were calculated in patients with RS vs LS tumors after excluding patients with rectal tumors (5-year OS for RS vs LS tumors was 68.0% vs 77.2%, respectively, p = 0.38; 5-year RFS for RS vs LS tumors was 62.8% vs 59.2%, respectively, p = 0.98). Conclusions: In contrast to sporadic CRC, PTS does not appear to have a prognostic role in IBD-CRC. Highlights: This the first study to investigate the prognostic value of primary tumor sidedness in patients with IBD-CRC. The results diverge from the findings of most studies that assessed primary tumor sidedness in sporadic CRC. The prognostic role of primary tumor sidedness in IBD-CRC is at the very least less pronounced than in sporadic CRC.